Mr neurography of median nerve using diffusion tensor imaging (DTI) and its efficacy to diagnose carpal tunnel syndrome in Malaysian population - Paniandi, Vikneswary; George, John; Goh, Khean Jin; Tan, Li Kuo (ASEAN Neurological Association, 2018)
Objective: This study evaluates the feasibility of diffusion tensor imaging(DTI) in assessing median nerve by measuring diffusion parameters such as fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD) at different sites of median nerve and evaluating their differences in patients with and without carpal tunnel syndrome (CTS) in local setting. Methods: A prospective cross sectional study was performed with 9 female patients diagnosed with CTS by clinical evaluation and nerve conduction study and 8 age and sex matched normal patients. Magnetic resonance imaging (MRI) wrist was performed with pre-set axial PD and DTI protocol on a 3T MRI, images post-processed using 3D SLICER software to generate median nerve tract and measure diffusion parameters FA, MD, AD and RD in segments and focal points. Results: The FA values were significantly lower in CTS patients, 0.454 (± 0.065), p< 0.002 and demonstrates negative correlation with disease severity, r = - 0.510, p = 0.002.The mean MD, 1.090 (± 0.178) and mean RD, 0.834 (± 0.128) is higher in CTS patients, p = 0.041 and p = 0.014 respectively. They show an increasing trend with increasing disease severity. Negative correlation was noted between the FA values and age groups. FA cut of value of ≤ 0.487 with sensitivity 70.6 % and specificity 76.5%, is suggested for diagnosing CTS. Conclusion: MR neurography using DTI can be utilised to detect CTS. Patients with CTS demonstrate lower FA and higher MD and RD values.